Hubungan Lama Penggunaan Kontrasepsi Hormonal Suntik DMPA dengan Kejadian Disfungsi Seksual, Literature Review - Dian Aby Restanty; Aprilina Aprilina; Ida Prijatni (Puslitbang Sinergis Asa Professional, 2022)
The biggest use of contraceptives in Indonesia is 3-month injectable contraceptives, 3- month contraceptives containing Depo Medroxyprogesterone acetate (DMPA) where long-term use of DMPA contraception results in sex hormone deficiency so that the acceptor experiences sexual dysfunction in aspects of sexual desire (libido) and intercourse pain. The purpose of this study was to analyze the relationship between the long use of DMPA injectable hormonal contraceptives with the incidence of sexual dysfunction in acceptors based on literature studies. The study used is a literature study with the type of Systematic Mapping Study. Articles are taken from databases in the form of Google Schoolar and Elsevier. The population obtained from the database was 23 articles, then screened using the PEOS framework and obtained as many as 5 articles consisting of four national articles and one international article. The results of the analysis of 5 articles found that the duration of DMPA use >2 years was 52.6% and 61.8% experienced sexual dysfunction. The results of the analysis test on the five articles showed that there was a 100% relationship between the duration of using DMPA injectable contraception and the incidence of sexual dysfunction. DMPA injection family planning acceptors should pay attention to the duration of use to reduce long-term risk, one of which is sexual dysfunction.